PENETRASI AGAMA NEGARA PADA KOMUNITAS TENGGER DI KANTONG TAMAN NASIONAL BROMO-TENGGER-SEMERU - Hadi, Nur (Jurnal Sejarah dan Budaya, 2009)
Abstract: After the cupdeta of communist party in 1965, there was massive effort of non-Tengger ethnic community to penetrate the nationâs religions (Hindu, Budha, Christian, and Islam) into the Tengger ethnic community who were considered as âno-religionâ ethnic. Consequently, the Tengger people who had already believed in âBudoâ as the only accepted Tenggereseâs religion had to be able to converse their religion. The phenomenon caused the emergence of âsincretismâ between their original religion and the nationâs religion with all consequences. The condition, in certain cases, needs to get much attention related to the change of traditional ritual of mountain society with its own local wisdom.